MODEL KONSELING QURANI UNTUK MENGEMBANGKAN FITRAH MANUSIA MENUJU PRIBADI KAAFFAH : Uji Coba Pada Mahasiswa Jurusan Bimbingan Dan Konseling Semester Ganjil Tahun 2005 Fakultas Ilmu Pendidikan Universitas Negeri Semarang - Anwar Sutoyo, - (2006)
ANWAR SUTOYO, 2006. "The Quranic Counseling Model to Develop the Fitrah of Human Beings towards the Kaaffah Personality" (The Trying-Out at the Even Semester of Year 2005 Students of the Educational Sciences Faculty of Semarang State University) This research is based on the reality that human beings since they were born have the Ftrah, in the form of iman, that encourage them to do the right things. But in the reality, most of the adult and educated humans deviate from the right behaviour. This may appear because their fitrah neither develop nor function wsll, because their education background is not based on the fitrah given by Allah the Almighty. Neglecting the fitrah will cause the missey and poverty individually and socially. So it is very necessary to develop the Fitrah through the counselling model based on the Quran. Many experts view that the fitrah is very important. Unfortunately only few experts are concerned with. So it is necessary to study who the human being is, what the purpose of the human being created by Allah is, what the Fitrah of human being is and how to develop the fitrah through a model. By answering those problems, it is expected that we can create the Quranic counseling model to develop the fitrah of human beings itself towards the kaafah personality. The research involves (1) the study of maudhu'i exegesis to get information about what human is and what the characteristics are, (2) implementation or trying-out model counseling model which concentrates on developing to the fitrah of human beings, (3) strategic improvement model. The research has been done through some steps, (1) book research (maudhu'i exegesis), through this step we get the information of Counseling (hypothetic) model to develop the fitrah of human beings based the Quranic perspective, (2) seminar involving the experts of couseling, psycholoy, and Islam. On this step we create the tentative couseling model, and (3) trying-out model This step leads us to create the Quranic Counseling Model and the appropriate strategy which can be applied in the real life.The results of the study involve (1) the findings of the, Quranic Counseling Model arranged based on the study of maudhu'i exegesis and the need analysis, (2) the findings of the essence of the fitrah of human beings, the firm pilars, the characteristics of individual with well developed fitrah and having the kaafah personality, the characteristics of the kaafah personality of individual, inhibiting and supporting factors, and things that an individual should do to develop his or her fitrah (3) the strategy of the Quranic Counseling Model application to develop the fitrah of human beings towards the kaafah personality, (4) The religiousity level of the students of Guidance and Counseling Department of Educational Sciences Faculty of Semarang State University shows that most of them have wrong understanding on the Islamic teaching, do not do daily activities based on the Islamic rules, have not been able to get the goodness beyond the worship to Allah, (5) The implication is that counseling is an effort to help a person leam to develop or to be back to his or her fitrah in order to get the hapiness on the earth and in the hereafter. This research recommands that (1) researchers in the future can dig up the model of developing the fitrah from the Quran more deeply, (2) researhers in the future can continue this reseach with larger population so it can be found the standard counseling model, (3) If this model is used, counselors and clients should be muslims, the counselors should understand the islamic teaching deeply, the counselor should show the charitable deeds so they can be a model or example for their clients, and always study the Islamic teaching truly.